2021
DOI: 10.1089/tmj.2020.0380
|View full text |Cite
|
Sign up to set email alerts
|

Caring for the Most Vulnerable: A Model for Managing Maladaptive Behavior in Children with Mental Special Needs During the COVID-19 Pandemic

Abstract: Background: This article presents the results of a comprehensive national model developed for managing maladaptive behaviors (MBs) in children with mental special needs (CMSNs) during the coronavirus disease 2019 (COVID-19) pandemic that combines telehealth-based Applied Behavioral Analyses, psychiatric interventions, and support from local psychosocial teams. This study aims to determine the effectiveness of a system that combined telehealth applications with local psychosocial support teams, allowing service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…The remaining papers were focused on behaviour programmes (e.g. behaviour counselling, applied behavioural analysis therapy; n = 9), [54][55][56][57][58][59][60][61][62] speech and language therapy (n = 4), [63][64][65][66] physiotherapy (n = 3), 53,67,68 mental health support (n = 2), 69,70 auditory-verbal therapy for children and young people with a hearing impairment (n = 1), 71 rehabilitative therapy for children and young people with vision impairment (n = 1), 72 and early intervention coaching (n = 1). 73 The percentages of families reporting attending a telehealth appointment with an AHP tended to be lower (less than 50% of study samples) than those reported for medical care appointments (over 50% of study samples).…”
Section: Frequency Of Consultationsmentioning
confidence: 99%
“…The remaining papers were focused on behaviour programmes (e.g. behaviour counselling, applied behavioural analysis therapy; n = 9), [54][55][56][57][58][59][60][61][62] speech and language therapy (n = 4), [63][64][65][66] physiotherapy (n = 3), 53,67,68 mental health support (n = 2), 69,70 auditory-verbal therapy for children and young people with a hearing impairment (n = 1), 71 rehabilitative therapy for children and young people with vision impairment (n = 1), 72 and early intervention coaching (n = 1). 73 The percentages of families reporting attending a telehealth appointment with an AHP tended to be lower (less than 50% of study samples) than those reported for medical care appointments (over 50% of study samples).…”
Section: Frequency Of Consultationsmentioning
confidence: 99%
“…the answers to this question (yes / no) were examined, 204 children said 'yes', and 299 adolescents said 'yes', and there was no difference between the groups in terms of activities (p=0.260). The answers to the open-ended question asked to those who answered 'yes' are shown separately in the child and adolescent group in graph form (Figure 1 (24). In addition, these results will help clinicians to predict the longterm consequences of symptoms seen in the early stages of pandemic.…”
Section: Activities and New Hobbies In The Lockdownmentioning
confidence: 99%
“…In cases of children with special needs, intervention was considered necessary in anticipation of problems resulting from home isolation and the disruption of daily routines, as well as additional behavioral problems expected with the increased emotional and physical burdens on families. A new approach for individuals with special needs, including an application that can be used on mobile devices, has been developed ( 7 ). With the application “Special Children Support System”, children with special needs whose behavioral problems worsened during the pandemic and their families have been provided with a support system based on applied behavioral analysis staffed by volunteer mental health workers and educators.…”
Section: Covid-19 and Child Mental Health In Turkeymentioning
confidence: 99%